Coming Back Into Existence Following Burn Injury: An Evolutionary Concept Analysis - Faranak Jabbarzadeh Tabrizi; Mojgan Lotfti; Vahid Zamanzadeh; Leila Valizadeh; Farzaneh Bagheriyeh; Geoffrey Dickens (Kerman University of Medical Sciences, 2021)
Introduction: Coming back into existence is a concept coined relatively recently in a grounded nursing theory of post-burn patients. However, the nature of this concept has not been thoroughly clarified. In order to improve nurses' and others' understanding of and communication about coming back to existence, this study aimed to clarify the concept.Methods: This study was performed qualitatively using Rodgers' evolutionary concept analysis to clarify the concept of coming back to existence. Multiple computerized databases (PubMed, Scopus, ProQuest, Google Scholar, Iran Mede, and SID) were searched for their titles and abstracts to select full-text English papers published without time limit. A total of 20 articles were selected to be reviewed.Results: The key attributes of coming back into existence identified in this study were providing opportunities for thinking and self-reflection on living affairs, releasing the mind to focus on the inner life, and making conscious efforts to explore and discover the original dimensions of one's being. Antecedents included the bitter and unforgettable experience of physical pain, psychological suffering, failure and hopelessness in interactions, and doubts about one's self-identity and philosophy of being. Consequences included self-acceptance, a sense of liberation and freedom, and positive and creative development in life to achieve more transcendent goals. Conclusion: The results of this study can be helpful in identifying the needs and problems of clients and developing appropriate care plans and nursing interventions.